Pentingnya Mendesain Pembelajaran Menuju Pendidikan Berkualitas - I Made Putra Aryana (Cetta: Jurnal Ilmu Pendidikan, 2020)
This article aims to put forward the learning design so that learning runs well, accompanied by anticipatory steps to minimize the gaps that occur so that learning activities achieve the goals set. The writing of this article uses the literature study method taken from various sources about learning. A teacher needs to have the ability to design and implement a variety of learning strategies that are considered suitable with the interests, talents and in accordance with the level of student development, including utilizing various sources and learning media to ensure the effectiveness of learning. The essence of learning design is the determination of optimal learning methods to achieve the stated goals. There is no learning model that can provide the most effective recipe for developing a learning program. The determination of the design model to develop a learning program depends on the designer's consideration of the model to be used or chosen. The educational process is a series of efforts to guide, direct the potential of human life in the form of basic abilities and personal lives as individual and social creatures and in their relationship with the natural surroundings to become responsible individuals.